Studies on response of seed quality parameters and chemical composition to nitrogen and sulphur nutrition in linseed (Linum usitatissimum) varieties: Studies on response of seed quality parameters and chemical composition to nitrogen and sulphur nutrition in linseed (Linum usitatissimum) varieties - A M MISAL; A V PAWAR (Journal of Oilseeds Research, 2023)
A field experiment was carried out to evaluate the effects of different levels of nitrogen (0,40,60 kg/ha) and sulphur (0,25,50 kg/ha) on linseed varieties viz. LSL-93 and NL-260. The results indicated that the growth attributing characters like chlorophyll content; seed quality parameters like germination and vigour index were enhanced with the supply of nutrients, resulting in better growth of the crop. The nitrogen and sulphur content of seed were also improved and found highest with the application of N@ 60 kg/ha and S@ 50 kg/ha. The treatment combination, V1N3S3 (LSL-93:N60:S50) was found to be the most effective amongst all the eighteen treatments.